Correction: Recent advances in the synthesis of analogues of phytohormones strigolactones with ring-closing metathesis as a key step. Issue 38 (21st September 2017) - Lombardi, Chiara; Artuso, Emma; Grandi, Eleonora; Lolli, Marco; Spyrakis, Francesca; Priola, Emanuele; Prandi, Cristina
Abstract : Correction for 'Recent advances in the synthesis of analogues of phytohormones strigolactones with ring-closing metathesis as a key step' by Chiara Lombardi, et al., Org. Biomol. Chem., 2017, DOI: 10.1039/c7ob01917c.